Dynamics of Sufism and Environment Studies in Indonesian Islamic Higher Education Institutions - Bambang Irawan; Ismail Fahmi Arrauf Nasution (Millati: Journal of Islamic Studies and Humanities, 2020)
The purpose of this research is to examine the dynamics of Sufism and environmental studies in Indonesian Islamic higher education institutions through scientific works in the form of a thesis, thesis, and dissertation. The selection of scientific works related to Sufism and the environment is made randomly. This research is classified as library research because it relies on collecting and analyzing data through literature studies. The data obtained were processed using discourse analysis and document analysis or content analysis. The data collected through inventory and documentation will be described in more detail by investigating the sources and literature on Sufism and environment relation. The finding of this study is even though scientific studies on Sufism and the environment is abundant, it has not yet had a significant influence on the development of teaching materials and nor directly proportional to the syllabus of Sufism courses.